Universal Social Pensions Are Unaffordable … Not! Testing the Unaffordability Hypothesis in Latin America and the Caribbean. Issue 1 (2nd January 2022) - Cruz-Martinez, Gibran
Abstract: Is universal social assistance unaffordable? Targeting social policy has been praised as a magic solution to select the 'deserving poor' and efficiently use the scarce resources in the Global South. The article tests the unaffordability hypothesis using five counterfactual analyses based on expenditure redirection (military expenditure, energy subsidies, and the potential illegal/odious external debt servicing) and increasing tax revenues (income and trade tax) in up to thirty-three countries. The article shows the revenue-generating potential of taxes and reprioritising expenditures from unproductive to productive areas to finance – totally or partly- basic universal social pensions in large part of Latin America and the Caribbean; therefore, dispelling the unaffordability myth.